2022
DOI: 10.3389/feart.2022.766145
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Simulation of Burial Diagenesis and Subsequent 2D-3D Characterization of Sandstone Reservoir Quality

Abstract: Characterization of deeply buried sandstones and their reservoir quality is of paramount importance for exploring, developing, and subsurface storage of energy resources. High reservoir quality in deeply buried sandstones is commonly correlated with the occurrence of grain coatings that inhibit quartz cementation. The development of reliable models that can predict reservoir quality relies on incorporating quantitative understanding of these diagenetic processes. Hydrothermal experiments simulating burial diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Authigenic chlorite coatings were hydrothermally synthesized on detrital quartz and feldspar grains (e.g., Figures 8B, 9C), and where coatings are absent, quartz and albite overgrowths were formed, respectively (e.g., Figures 11C, D, 12A, B). The experiments have shown that the physical obstruction of nucleation sites by the clay coats is an effective mechanism by which the development of ubiquitous quartz and albite overgrowths can be inhibited (Aagaard et al, 2000;Ajdukiewicz and Larese, 2012;Haile et al, 2015;Charlaftis et al, 2021;Charlaftis et al, 2022).…”
Section: Experimental Development Of Clay and Microquartz Coatingsmentioning
confidence: 99%
“…Authigenic chlorite coatings were hydrothermally synthesized on detrital quartz and feldspar grains (e.g., Figures 8B, 9C), and where coatings are absent, quartz and albite overgrowths were formed, respectively (e.g., Figures 11C, D, 12A, B). The experiments have shown that the physical obstruction of nucleation sites by the clay coats is an effective mechanism by which the development of ubiquitous quartz and albite overgrowths can be inhibited (Aagaard et al, 2000;Ajdukiewicz and Larese, 2012;Haile et al, 2015;Charlaftis et al, 2021;Charlaftis et al, 2022).…”
Section: Experimental Development Of Clay and Microquartz Coatingsmentioning
confidence: 99%